2017
DOI: 10.3390/ma10050544
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Modeling and Genetic Algorithm Optimization for Cadmium Removal from Aqueous Solutions by Reduced Graphene Oxide-Supported Nanoscale Zero-Valent Iron (nZVI/rGO) Composites

Abstract: Reduced graphene oxide-supported nanoscale zero-valent iron (nZVI/rGO) composites were synthesized in the present study by chemical deposition method and were then characterized by various methods, such as Fourier-transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). The nZVI/rGO composites prepared were utilized for Cd(II) removal from aqueous solutions in batch mode at different initial Cd(II) concentrations, initial pH values, contact times, and operating temperatures. Response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 70 publications
1
28
1
Order By: Relevance
“…Dry dichloromethane and phosphorous pentachloride were added to GO and mixed to yield a highly sensitive and stable composite for the adsorption of nickel [122]. [116]. These values compare favorably with reported values for other adsorbents but are not as high as certain ion exchangers.…”
Section: Nickel Removalsupporting
confidence: 67%
See 1 more Smart Citation
“…Dry dichloromethane and phosphorous pentachloride were added to GO and mixed to yield a highly sensitive and stable composite for the adsorption of nickel [122]. [116]. These values compare favorably with reported values for other adsorbents but are not as high as certain ion exchangers.…”
Section: Nickel Removalsupporting
confidence: 67%
“…Dry dichloromethane and phosphorous pentachloride were added to GO and mixed to yield a highly sensitive and stable composite for the adsorption of nickel [122]. The reported capacities of 76, 104, 181 mg Ni (II)/g GO are linked to the high initial adsorbate concentrations of 51, 60, 100 mg/L, respectively [116]. These values compare favorably with reported values for other adsorbents but are not as high as certain ion exchangers.…”
Section: Mercury Removalmentioning
confidence: 57%
“…The ANNs can solve multivariate non‐linear problems with a suitable amount of data and an appropriate training algorithm (Zhang and Pan , Fan et al. , López et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The Langmuir model indicates a monolayer coverage on the surface of the adsorbent, while the Freundlich model is indicative of the surface heterogeneity of the adsorbent [ 53 , 54 ]. In this study, the isotherm plots for the Hg ion adsorption are shown in Figure S11 , and the regression coefficients ( R 2 ) of the Langmuir and the Freundlich models obtained by linear fitting were 0.9049 and 0.9118, and those obtained by nonlinear fitting were 0.8775 and 0.9118 ( Table 2 ), respectively.…”
Section: Resultsmentioning
confidence: 99%